The Dispute of Flirtation and Enthusiasm in Pre-Islamic Poetry An Objective Artistic Study For Teaching Arabic Literature/ جدلية الغزل والحماسة في الشعر الجاهلي دراسة موضوعية وفنية لتعليم الأدب العربي - Arif Abdullah Mahmoud (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Teaching Arabic, especially literature related to poetry, must also teach the character of Arabic writers. The flirtation movement was mixed with enthusiasm because it is found in all atmospheres, even in the poems of love, especially when it grows stronger and becomes the beloved in the comedy of heroism. For example, Antarah bin Shaddad, who collected the sword and the arrows, stabbed the honey in an atmosphere in which war and love were mixed for the sake of highness and the sublime (Al-Baldawi). Therefore, we find his poetry strong, devoid of softness and tenderness because he lived in the atmosphere of war, suffering, and the cruelty of its conditions. Thus, his language is enthusiastic, intense, and lacks indolence. The Arabic people are the sons of their environment. They are knights who stretch in the desert (the Arabian Peninsula) with all dignity and pride, confident in step, strong-willed, basking in the whims of freedom and fulfillment. The Arabs are assertive and do not slacken in the face of adversity, no matter the sacrifices it costs. This is how they love life and land—singing in it the hymn of war and flirting with those on it with the passion of love. It was a subject that occupied the interest of the pre-Islamic poets until they issued it at the beginning of his poems. That nature of art which is a psychological need, represents facts and consciousness as it is. The spirit of life awakens a person's sense of meanings that cannot be hidden or ignored, no matter how great or magnificent it is, because it is part of his breath (Abdullah). Thus, the psyche of the knights' poets was a song sung by the poem of love following the blockages and desertions they are experiencing and the separation or departure that makes them sleepless. It also provokes their anger towards those they love, as they convey their complaints in an unbearable alienation, continuing to talk about their suffering in search of solutions to resolve their crises and seeking to deal with the sad things (Abdel-Baqi).